Comparative Analysis of Intracellular and in vitro Antioxidant Activities of Essential Oil From White and Black Pepper (Piper nigrum L.) - Ying Wang; Liang Wang; Jin Tan; Rong Li; Zi-Tao Jiang; Shu-Hua Tang (Frontiers Media S.A., 2021)
Ethnopharmacological Relevance: Pepper essential oils have potential immunomodulatory, anti-tumor, and anti-cancer activities. Pepper exhibits the potential to prevent or attenuate carcinogenesis as therapeutic tools. However, the related mechanism remains unelucidated.Aim of the Study: The present study aims to provide reasonable information for the explanation of the dissimilarity of the essential oils from white (WPEO) and black pepper (BPEO).Materials and Methods: WPEO, BPEO, and their single active component, as well as synthetic antioxidants, were compared by the cell model methods and chemical methods, including intracellular antioxidant activity (CAA), total antioxidant activities (TAA), superoxide radical (SR), hydroxyl radical (HR), DPPH radical (DR) scavenging activities and inhibition ability of lipoprotein lipid peroxidation (ILLP).Results: The median effective concentration (EC50) values (mg/mL) of the WPEO and BPEO of SR, HR, DR, and ILLP were 0.437 and 0.327, 0.486 and 0.204, 7.332 and 6.348, 0.688, and 0.624 mg/mL, respectively. The CAA units of WPEO and BPEO were 50.644 and 54.806, respectively. CAA, DR, and TAA of BPEO were significantly higher than those of WPEO (p < 0.05). The BPEO and WPEO can be differentiated as the former have higher correlations with 3-carene, α-pinene, β-pinene, and limonene while the latter has a higher caryophyllene correlation. The WPEO and BPEO show a good intracellular scavenging ability of reactive oxygen species in HeLa cells.Conclusion: Generally, pepper oil has stronger activities than single components, indicating that pepper is a broad-spectrum natural antioxidant.